Preface: Aerosol research at SMEAR stations. - Kulmala, M.; Hari, H.; Vesala, T. (Boreal Environment Research Publishing Board, 2024)
This issue is the first of the two special issues related to the research activities at SMEAR (Station for Measuring Forest Ecosystem-Atmosphere Relations) stations. The SMEAR I station, located in Värriö, has been in operation since 1991 and the SMEAR II station, located in Hyytiälä, since 1995. The second special issue will be published in next year with focus on the forest-atmosphere relationship and forest ecology. Both the issues are based on the presentations given in the APFE (Aerosol Physics & Forest Ecology) seminar during 7–9 February 2000. The SMEAR stations are operated by the APFE group. The APFE group consists of ca. 50 scientists and is one of the centres of Excellence in the University of Helsinki. The aerosol research in the SMEAR stations has focussed on the formation and growth of atmospheric aerosols, particularly the nucleation-mode aerosols. Annually around 50 new-particle formation events have been observed with subsequent growth to the Aitken and even to the accumulation mode. These observations have motivated us to study mechanisms behind these formation events. These phenomena have been investigated from physical, chemical, meteorological, and biological points of view. Clear connections have been found between the formation events and e.g. meteorological conditions, aerosol physical and atmospheric chemical conditions, and biological activities. This issue with six papers is a compact demonstration of the aerosol research conducted within the APFE group. The main features of aerosol formation events are reported in the first four papers. The fifth paper describes a development and construction of a Cloud Condensation Nuclei Counter, and in the last paper a new model development is presented. We would like to thank all authors for their contribution and acknowledge the Academy of Finland and University of Helsinki for their financial support.